Smart Lab Energy – For Real-Time Electricity Consumption Monitoring In The Electronics Engineering Technology Laboratory, Polytechnic State Of Lampung - Tomy Pratama Zuhelmi; Novia Utami Putri; Ayu Sintianingrum; Syaiful Mansur; Ernando Rizki; Amanda Putri Denizka; Altino Adni Riyadi (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2026)
This study aims to design and implement an Internet of Things (IoT)-based electrical energy monitoring system capable of displaying real-time data in a vocational education laboratory environment. The developed system utilises an ESP32 microcontroller and a PZEM-004T sensor to accurately measure voltage, current, power, and energy parameters. The measurement data are transmitted to a cloud server and visualised through a digital dashboard, allowing users to monitor and analyse energy usage easily. The test results show that the system performs well and produces consistent data compared to manual measurements using a digital clamp meter. The implementation of this system has the potential to improve energy efficiency, reduce power waste, and support the application of a green campus concept in higher education institutions. Moreover, this system can be used as a project-based learning medium to enhance students’ competencies in embedded systems, sensors, and IoT-based automation.